Impact of Disability Placements on Allied Health Students: Placement Educators’ Perspectives - Nagarajan, Srivalli; Chung, Alison; Trede, Franziska; McAllister, Lindy (International Journal of Practice-based Learning in Health and Social Care, 2017)
Research on the relevance of placements to the development of allied health student skills to work with people with disability, is an underexplored area. This knowledge is important for several reasons: to prepare students for disability placements, develop their work readiness skills to work with people with disability upon graduation, inform placement curriculum development, and ensure placement educators are supported to provide effective and efficient supervision of students on disability placements. The study discussed in this article, explores placement educators’ perceptions of powerful learning experiences during disability placements that shape students’ attitudes and perceptions of working with people with disability. Allied health placement educators from three Australian disability organisations, were invited to attend focus groups on this topic. Two focus groups, with a total of seven participants, were conducted in February and May 2016. The allied health disciplines represented in the focus groups were Speech Pathology, Occupational Therapy, and Physiotherapy. Thematic analysis technique was used to analyse focus group data. Findings related to the following four key topic areas, are discussed in this article: a. Reasons for placement educators entering and staying in the disability sector; b. Placement educator perceptions of changes in student attitudes and skills post disability placements and how their experiences shape their approaches to student placement education; c. Recommendations for universities to better prepare students to work with people with disability; and d. Preparation of students for job-seeking in the disability sector.